Asia's water crisis [videorecording] the struggle within each drop - Kalin, Andrea; Westfall, Matthew; Blair, Nicholas (Asian Development Bank, 1997)
More than 1 billion people in developing world lack access to safe drinking water, and more than 2.5 billion live without sanitation. In the countryside, farmers use two thirds of their water to irrigate their fields. In Asia's teeming megacities, water needs of growing urban populations compete with expanding industries and agriculture. Over the next 15 years, one billion more people will have to share Asia's scarce water supplies.